Insecticide Rotation and Adaptive Fitness Cost Underlying Insecticide Resistance Management forSpodoptera frugiperda(Lepidoptera: Noctuidae) - Barbosa, M. G.; Andre, T. P. P.; Pontes, A. D. S.; Souza, S. A. [UNESP]; Oliveira, N. R. X.; Pastori, P. L. (Entomological Soc Brasil, 2020)
Rotation of insecticide modes of action is recommended to delay selection for insecticide resistance. In this study, larvae ofSpodoptera frugiperda(J.E. Smith) were exposed alternately to spinetoram and metaflumizone with insecticidal and biological response determined. Five generations (G) were evaluated with at least 200 larvae assayed per treatment. The experiment consisted of rearing field-collected and untreated larvae (M-Control), larvae with successive applications of either metaflumizone (M-MET) or spinetoram (M-SPI), and alternation of these insecticides (M-Rotation treatment) consisting of the following treatments: G(2) = exposure to SPI, G(3) = exposure to MET, G(4) = exposure to SPI, G(5) = exposure to MET, and G(6) = exposure to SPI. Four days after application, those surviving larvae were used to compose the following generations. In the G(7), evaluations were made on the selected populations M-MET, M-SPI, M-Rotation, and control larvae to determine biological characteristics used to calculate the fertility life table parameters and further comparisons across treatments. The frequency of resistance was increased at rate of 49.5% and 29.2% after five generations of selection pressure with MET and SPI, respectively. However, rotation of insecticides reduced the frequency of resistance about 50% over the generations. Individuals originated from successive exposures to the insecticides exhibited delayed egg incubation, greater percentage of pupae with deformation, longer larval and pupal periods, and reduction in emergence rate and longevity of adults, suggesting adaptive costs associated with resistance.
Keywords: Fall armyworm; chemical control; susceptibility; life history; resistance monitoring